SUSCETIBILIDADE E DANOS CAUSADOS A ESPÃ‰CIES DE ð˜Œð˜¶ð˜¤ð˜¢ð˜ð˜ºð˜±ð˜µð˜¶ð˜´ E ð˜—ð˜ªð˜¯ð˜¶ð˜´ POR NEMATÃ“IDES DAS GALHAS NO ESTADO DE SÃƒO PAULO - Ferraz, Luiz Carlos C. Barbosa; Lordello, Luiz Gonzaga E. (REVISTA DE AGRICULTURA, 2020)
SUSCETIBILIDADE E DANOS CAUSADOS A ESPÃ‰CIES DE ð˜Œð˜¶ð˜¤ð˜¢ð˜ð˜ºð˜±ð˜µð˜¶ð˜´ E ð˜—ð˜ªð˜¯ð˜¶ð˜´ POR NEMATÃ“IDES DAS GALHAS NO ESTADO DE SÃƒO PAULO